Effect of Herbal Liver Stimulants on the Performance of Hy-line Commercial Layer - Neupane, Damodar; Karki, Mukesh; Upreti, C. R.; Dhaubhadel, Tribhuveneshor (Nepal Journal of Science and Technology, 2010)
An investigation was undertaken on 180 day-old Hy-line layer chicks to assess the effect of herbal products on feed consumption, egg production and profitability. The experimental chicks were randomly divided in three groups with three replicates in each and were housed in identical management and environmental conditions. Dietary treatments were prepared by addition of herbal liver stimulants such as Livoliv 250 @500 g/ton (D2) and Superliv @500g/ton (D3) in the basal diet (D1). Feed intake, egg production and mortality were recorded throughout the observation period of 50 weeks. Feed per unit of egg production, hen day percentage, additional income of supplemented diet over the basal diet were calculated. Average daily intake (g) of the diets per bird were observed as 59.19±1.05 g, 58.31±0.337 g and 57.67±0.163 g up to 20 weeks and 108.94±0.06 g, 109.01±0.05 g and 108.26±0.41 g during the laying period fed with D3, D1 and D2 diets respectively. Similarly, higher hen day egg % (76.9%) was recorded in the birds fed with Superliv supplemented diet (D3), followed by Livoliv supplemented diet (D2) (73.4%) and Basal diet (D1) (72.1%) with feed intake per unit egg production of 179.3 g, 178.1 g and 193.0 g, respectively. Total egg production was found higher with D3 (161.49 egg), followed by D2 (154.15 egg) and basal diet (151.45 egg) with layer house cumulative mortality only in D3 (3.75%). Additional profits of Rs. 35.18 and Rs. 12.86 in terms of egg selling over feed cost per layer were calculated for the bird fed with Superliv supplemented diet (D3) and Liveloliv supplemented diet (D2) than that of the basal diet. Key words: layer; herbal products; liver stimulant; feed efficiency; profit DOI: 10.3126/njst.v9i0.3162 Nepal Journal of Science and Technology 9 (2008) 37-40